Pengembangan Model Pembelajaran Sejarah SMA Berbasis Pendidikan Karakter di Solo Raya - Leo Agung S. (Jurnal Pendidikan dan Kebudayaan, 2012)
This exploratory study aims to: 1) determine objectives, materials, methods, media and evaluation of history teaching in senior secondary schools; 2) identify factors that support and inhibit history teaching in senior secondary schools; 3) exploit the understanding of history teachers of senior secondary schools on history teaching models; and 4) establish a model for character education based-history learning. Research subjects are history teachers of senior secondary schools in Solo Raya. Data were collected using observation, interviews, document analysis, questionnaire and Focus Group Discussion techniques, and analyzed using the method of qualitative interactive model. The results showed that: 1) purpose of history teaching inculcate the spirit of nationalism, love of nation and homeland; materials in accordance with the Content Standards; lecture methods varies, power point media, film and Liquid Crystal Display, while the evaluation is still tend to focus on cognitive aspects; 2) supporting factor of history teaching is the development of innovative learning models, while the inhibiting factors are the lack number of BSE book and discrimination on the subjects; 3) majority of history teachers of senior secondary schools have understood the learning models, and 4) completion of the Critical, Creative, Chain and Character model (KKBB). ABSTRAKPenelitian eksploratif ini bertujuan untuk: 1) mengetahui tujuan, materi, metode, media, dan evaluasi pembelajaran Sejarah di Sekolah Menengah Atas (SMA); 2) mengidentifikasi faktor-faktor pendukung dan penghambat pembelajaran Sejarah di SMA; 3) mengeksploitasi pemahaman guru-guru Sejarah di SMA terhadap model-model pembelajaran Sejarah; dan 4) menyusun model Pembelajaran Sejarah Berbasis Pendidikan Karakter. Subjek penelitian adalah guru-guru Sejarah SMA Solo Raya. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, analisis dokumen, angket dan Focus Group Discussion. Metode analisis data menggunakan analisis kualitatif model interaktif. Hasil penelitian menunjukkan, bahwa: 1) tujuan pembelajaran Sejarah menanamkan semangat kebangsaan, cinta bangsa dan tanah air; materi sesuai dengan Standar Isi; metode ceramah bervariasi, media power point, film dan Liquid Crystal Display, sedangkan evaluasinya masih banyak pada aspek kognitif; 2) Faktor pendukung pembelajaran Sejarah, yaitu adanya model-model pembelajaran inovatif, faktor penghambatnya buku BSE yang minim, dan adanya diskriminatif mata pelajaran; 3) sebagian besar guru-guru SMA telah memahami model-model pembelajaran; dan 4) tersusunnya model Kritis, Kreatif, Berantai dan Berkarakter (KKBB).